Faktor Risiko Kejadian Diabetes Melitus Tipe 2 pada Pegawai Pemerintah di Indonesia: (Analisis Data SKI Tahun 2023) - Plenti Greis Sitanggang; Ummi Kalsum; Evy Wisudariani; Rd. Halim; Helmi Suryani Nasution (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
The prevalence of type 2 DM in Indonesia increases every year and becomes an important issue, especially for government employees who are vulnerable to various risk factors. This study aims to analyze the risk factors associated with the incidence of type 2 DM in government employees in Indonesia. The study used secondary data from the 2023 Indonesian Health Survey with a cross-sectional design. The population of this study consisted of 877,531 respondents and a sample of 30,631 respondents. The variables studied included age, gender, education, hypertension, smoking, stress, and socioeconomic status. The analysis was carried out using the complex samples chi-square test. Statistical tests show results ​​for the variables age (p = 0.000), gender (p = 0.018), education (p = 0.087), hypertension (p = 0.000), smoking (p = 0.05), stress (p = 0.000), and socioeconomic (p = 0.000). There is a relationship between age, gender, hypertension, smoking, stress, and socioeconomic with the incidence of type 2 DM in government employees in Indonesia. There is no relationship between education and the incidence of type 2 DM in government employees in Indonesia. Efforts are needed to change a healthy lifestyle for government employees to reduce the risk of type 2 diabetes.